ANALISIS ANTIOKSIDAN, TOTAL ASAM, TOTAL PADATAN TERLARUT DAN VISKOSITAS PADA MINUMAN SIROP JERUK SIAM (Citrus nobilis var. microcarpa): Analysis of antioxidants, total acid, total dissolved solid and viscosity of siam orange syrop drink (Citrus nobilis var. microcarpa) - Dian Sari; Ee Zurmansyah; Hamdi Hamdi; Kiki Kristiandi (PAKIS JOURNAL INSTITUTE, 2023)
Syrup drink is a drink that is much favored by various circles of society after water and coffee. Many syrup drinks are served in various activities because the taste that is generated gives a sense of freshness. The syrup made in this research is Siamese orange syrup. The purpose of this study was to analyze the antioxidant content, total acid, total dissolved solids, and viscosity in Siamese orange syrup. This research uses the juice produced from Siamese oranges and this research takes place from November 2020 – February 2021. The processing process to get the juice is carried out at the Food Agroindustry Laboratory of the Sambas State Polytechnic. And the results of the tests carried out in Sucofindo with sample testing using the AOAC method (2016) ed. 20. The results obtained in the test of Siamese orange syrup are 18,542 mg/L (IC50) ) for antioxidants, 0.54% for total acid, 11.09 0Brix for total dissolved solids and a viscosity of 7.121 Cp. Based on the test results on the Siamese orange syrup drink, the processed Siamese orange can be said to be a drink that complies with market standards in general.